PENGUNAAN GAMELAN BHATARA BAGUS SELONDING DALAM TRADISI MEGERET PANDAN DI DESA TENGANAN PEGRINGSINGAN KECAMATAN MANGGIS KABUPATEN KARANGASEM: Perspektif Teologi Hindu - Gusnadi, Gusti Ngurah Arya; I Nyoman Subrata; I Nyoman Piartha (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2024)
Gamelan Bhatara Bagus Selonding is a gamelan which is sacred by the people of Tenganan Pegringsingan Village. Gamelan Bhatara Bagus Selonding has an important role in religious activities in Tenganan Pegringsingan Village, especially in the Megeret Pandan tradition. This research was formulated in 3 problems, namely: 1) What is the shape of the Bhatara Bagus Selonding Gamelan instrument in the Megeret Pandan Tradition in Tenganan Pegringsingan Village, Manggis District, Karangasem Regency? 2) What is the function of Gamelan Bhatara Bagus Selonding in the Megeret Pandan Tradition in Tenganan Pegringsingan Village, Manggis District, Karangasem Regency? 3) What does the meaning of Gamelan Bhtara Bagus Selonding in the Megeret pandan Tradition in Tenganan Pegringsingan Village, Manggis District, Karangasem Regency?The problem is examined with three theories namely, the principle of religious principles, aesthetic theory, and symbol theory. The method used in this study is a qualitative method, the process consists of determining the location of research, using qualitative data sourced from informants and relevant written sources, determining research instruments, informants are determined on a representative basis. Data collection through observation, in-depth interviews, literature study and documentation.The results showed that (1) The form of Bhatara Bagus Selonding Gamelan is slonding barungan tools including: 1) Atungguh Paenem, 2) Atungguh patuduh, 3) Atungguh nyongnyong Ageng, 4) Aungguh Nyongnyong Alit, 5) Atungguh Gong Ageng, 6) Atungguh Gong Alit, 7) Atungguh Kempul Ageng, 8) Atungguh Kempul Alit.2) The function of Bhatara Bagus Selonding is as a Superintendent and Pengerahan Megerert pandan. As forming the feeling of courage when playing Gending Kelor curry Gug-curry.3) The meaning contained in the Gamelan Bhatara Bagus Selonding in the Megerert Pandan Tradition is Gamelan Bhatara Bagus Selonding is very purified and made into God (God).